PERAN BIMBINGAN BELAJAR MATEMATIKA DALAM PENJUMLAHAN BILANGAN PADA SISWA KELAS 2 SD NEGERI JERUK SOKSOK 01 KECAMATAN BINAKAL: SD NEGERI JERUK SOKSOK 01 KECAMATAN BINAKAL - EDI WAGIANTO (Dewan Pendidikan Bondowoso, 2023)
This study aims to investigate the role of mathematics tutoring in adding numbers to grade 2 students at SD Negeri Jeruk Soksok 01 Binakal District. The method used in this study was an experiment with a pretest-posttest control group design. The sample of this research was 20 grade 2 students consisting of 10 students in the experimental group and 10 students in the control group. The experimental group was given tutoring in mathematics while the control group was not given tutoring. The instrument used in this research is the number addition test. The results showed that there was a significant difference between the pretest and posttest mean values of the experimental and control groups. In addition, the results of data analysis also show that mathematics tutoring has a significant role in improving students' numeracy skills. Therefore, it is suggested that mathematics tutoring continues to be improved and used as one of the important programs in improving the quality of learning mathematics at SD Negeri Jeruk Soksok 01 Binakal District.